Penerapan Sanksi Pemerintahan pada PT. Mirtasari Development - Putu Dyah Prastiti Sukma Febriany; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2021)
Of natural resources is the primary object for any development Countries Indonesia, thus unwittingly slowly at least not among them triggering pollution and/or destruction of the environment. Therefore, the need for law enforcement that is reflected in the legislation. The problem of this research were: 1 a complaints handling procedure) how pollution and/or destruction of the environment? 2) How the application of sanctions to force the Government in pt. Mirtasari Hotel Development? The type of research and the approach used is the juridical problems of empirical and juridical sociological. Source material source materials used law of law of primary and secondary sources of law. Legal materials collection techniques are used namely study library and field. As well as legal materials collected processed and analyzed with the use of legal argumentation. As for the results of this research are the complaints handling procedures due to contamination and/or destruction of the environment will be followed up by agencies or institutions or the PPLHD PPLH advance has received complaints directly or not direct, which is then followed up with several stages, namely: the stages of the preparation, the implementation of field verification, data analysis, and final verification report the complaint. The application of administrative sanctions the Government at PT. Mirtasari Hotel Development was given by the Minister of the environment in the form of the action force to immediately complete the related permit temporary storage of waste, waste water disposal B3, B3 waste submission to third parties, as well as complement the facilities by the rules in the temporary storage of waste B3.